Pengaruh Keadilan Prosedural terhadap Organizational Citizenship Behavior Melalui Persepsi Dukungan Organisasiona sebagai Variabel Mediasi : Studi Kasus pada Dinas Kelautan dan Perikanan Provinsi Sulawesi Selatan - Ahmad Ali Yassar Ranti; Siti Hasbiah; Sayu Puspitaningsih Dipoatmodjo; Zainal Ruma; Muhammad Ilham Wardhana Haeruddin (Pusat Riset dan Inovasi Nasional, 2025)
Organizational effectiveness depends not only on employees fulfilling their formal roles but also on their willingness to engage in discretionary efforts, known as Organizational Citizenship Behavior (OCB). Promoting OCB is essential not only for private organizations but also for public institutions, which have come under increasing public scrutiny. Despite this urgency, limited attention has been paid to how organizational-level factors such as procedural justice influence OCB in public institutions. The purpose of this study is to assess how procedural justice influences OCB through perceived organizational support as a mediating variable, particularly within public institutions; the Fisheries and Marine Affairs Agency of South Sulawesi Province in Indonesia was selected as the study’s object. A quantitative cross-sectional method was employed, with employees stationed at the head office serving as the sample. The findings suggest that procedural justice influences OCB both directly and indirectly through perceived organizational support, and that perceived organizational support significantly affects OCB. Therefore, perceived organizational support only partially mediates the relationship between procedural justice and OCB.